WASTEWATER TREATMENT BAKERY USING ACTIVE CARBON OF WATER HYACINT AND BOILER WASTE - Rita Dwi Ratnani; Afilina Yunas Ariyaningrum; Farikha Maharani (Universitas Wahid Hasyim, 2022)
Bakery industry wastewater usually comes from the washing process of production equipment and generally contains organic compounds, oils, fats, and surfactants. Efforts are needed to overcome these problems so that contamination due to bakery waste can be handled. This study aims to determine the ability of water hyacinth activated carbon and boiler waste activated carbon in improving the quality of wastewater through the adsorption process so that it is expected to be in accordance with the wastewater quality standards set by the Central Java Regional Government. The variables used are activated carbon mass, time, and temperature of the adsorption process. The results showed a change in color and odor, from greenish to clear, and a reduction in fishy odor in the wastewater. A decrease in COD value and an increase in pH also occurred, with the best results being obtained using activated carbon from boiler waste at a mass weight of 20 g, a time of 90 minutes, and a temperature of 45 °C. The best results are obtained by combining activated carbon from water hyacinth and boiler waste at a mass ratio of 1:19 g, a time of 120 minutes, and a temperature of 35 °C.Keywords: Bakery Industry Wastewater, Adsorption, Activated Carbon, Color, COD, pH